Metabolic and chromosomal changes in a Bacillus subtilis whiA mutant - Laura C. Bohorquez; Joana de Sousa; Transito Garcia-Garcia; Gaurav Dugar; Biwen Wang; Martijs J. Jonker; Marie-Françoise Noirot-Gros; Michael Lalk; Leendert W. Hamoen (Microbiology Spectrum, 2023)
ABSTRACT The conserved protein WhiA is present in most Gram-positive bacteria and plays a role in cell division. WhiA contains a DNA-binding motif and is a transcription regulator of the key cell division gene ftsZ in actinomycetes. In Bacillus subtilis, the absence of WhiA influences both cell division and chromosome segregation; however, the protein does not regulate any gene involved in these processes. In this study, we addressed three alternative mechanisms by which WhiA might exert its activity in B. subtilis and examined whether WhiA influences either (i) central carbon metabolism, (ii) fatty acid composition of the cell membrane, or (iii) chromosome organization. Mutations in glycolytic enzymes have been shown to influence both cell division and DNA replication. To measure the effect of WhiA on carbon metabolism, we tested different carbon sources and measured exometabolome fluxes. This revealed that the absence of WhiA does not affect glycolysis but does influence the pool of branched-chain fatty acid precursors. Due to the effect of WhiA on chromosome segregation, we examine chromosome organization in a ∆whiA mutant using chromosome conformation capture (Hi-C) analysis. This revealed a local reduction in short-range chromosome interactions. Together, these findings provide new avenues for future research into how this protein works in the non-actinomycete firmicutes. IMPORTANCE WhiA is a conserved DNA-binding protein that influences cell division in many Gram-positive bacteria and, in B. subtilis, also chromosome segregation. How WhiA works in Bacillus subtilis is unknown. Here, we tested three hypothetical mechanisms using metabolomics, fatty acid analysis, and chromosome confirmation capture experiments. This revealed that WhiA does not influence cell division and chromosome segregation by modulating either central carbon metabolism or fatty acid composition. However, the inactivation of WhiA reduces short-range chromosome interactions. These findings provide new avenues to study the molecular mechanism of WhiA in the future.